2014
DOI: 10.1155/2014/983016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Kir6.2 Subunit(KCNJ11)of Pancreatic ATP-Sensitive Potassium Channel Gene Are Associated with Insulin Response to Glucose Loading and Early Onset of Type 2 Diabetes in Childhood and Adolescence in Taiwan

Abstract: To investigate the role of E23K polymorphism of the KCNJ11 gene on early onset of type 2 diabetes in school-aged children/adolescents in Taiwan, we recruited 38 subjects with type 2 diabetes (ages 18.6 ± 6.6 years; body mass index percentiles 83.3 ± 15.4) and 69 normal controls (ages 17.3 ± 3.8 years; body mass index percentiles 56.7 ± 29.0) from a national surveillance for childhood/adolescent diabetes in Taiwan. We searched for the E23K polymorphism of the KCNJ11 gene. We found that type 2 diabetic subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
2
11
1
1
Order By: Relevance
“…Consistent with previous studies in populations with T2D, we showed in the present study that youth with prediabetes had a higher E23K carrier rate of KCNJ11 than normal subjects, and that K allele‐containing genotypes are independent risk factors for prediabetes in Chinese youth. However, in contrast with the study of Jiang et al we did not find that fasting insulin levels are independent risk factors for prediabetes in Chinese youth. Rather, we showed that lower insulin levels at 30 min during the OGTT are independent risk factors of prediabetes in Chinese youth, suggesting that impaired insulin secretion is a predictor of the development of prediabetes in Chinese youth.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Consistent with previous studies in populations with T2D, we showed in the present study that youth with prediabetes had a higher E23K carrier rate of KCNJ11 than normal subjects, and that K allele‐containing genotypes are independent risk factors for prediabetes in Chinese youth. However, in contrast with the study of Jiang et al we did not find that fasting insulin levels are independent risk factors for prediabetes in Chinese youth. Rather, we showed that lower insulin levels at 30 min during the OGTT are independent risk factors of prediabetes in Chinese youth, suggesting that impaired insulin secretion is a predictor of the development of prediabetes in Chinese youth.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, mutations of KCNJ11 can cause permanent hyperinsulinemic hypoglycemia of infancy . Although the association of the E23K polymorphism with type 1 diabetes was not statistically significant in Asian and European populations, it has been reported that E23K polymorphisms of KCNJ11 contribute to T2D in youth in Taiwan . Consistent with previous studies in populations with T2D, we showed in the present study that youth with prediabetes had a higher E23K carrier rate of KCNJ11 than normal subjects, and that K allele‐containing genotypes are independent risk factors for prediabetes in Chinese youth.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Так, носитель-ство аллеля 23Lys повышает риск развития СД2 в китайской [OR= 1,15 Таким образом, данные литературы и результа-ты наших исследований показывают, что поли-морфный локус Glu23Lys гена KCNJ11 является важным генетическим фактором риска развития СД2 как в азиатских, так и в европейских популяци-ях. Частота встречаемости аллеля риска -23Lys гена KCNJ11 в кыргызской популяции составляет 0,33 и существенно не отличается от таковой в дру-гих азиатских популяциях и среди европейцев (0,34-0,37) [12,[14][15][16][17].…”
Section: результаты и обсуждениеunclassified